EFEKTIVITAS PERAN MEDIATOR DALAM MENEKAN ANGKA GUGAT CERAI: ANALISIS YURIDIS EMPIRIS DI PENGADILAN AGAMA JOMBANG - M. Riziq Akbar Al Hafidz; Ahmad Faozan (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The high rate of divorce lawsuits (gugat cerai) at the Jombang Religious Court from 2022 to 2025 emphasizes the need for optimal dispute resolution. Although mediation is mandated by PERMA No. 1 of 2016 as a peaceful instrument, its overall success rate remains relatively low due to complex socio-economic issues. This empirical juridical study aims to analyze the effectiveness of mediators and the supporting and inhibiting factors influencing the process based on Soerjono Soekanto's legal effectiveness theory. Data were gathered through observation, in-depth interviews with judicial and non-judicial mediators, and documentary analysis, subsequently evaluated using descriptive qualitative methods. The findings indicate that while the formal implementation of mediation aligns with legal procedures, its effectiveness in curbing the divorce rate is constrained by the parties' lack of good faith, economic pressures, domestic violence, and the mediators' limited time due to heavy case backlogs. However, the application of humanistic communication strategies—such as triggering past romantic memories, optimizing the psychological layout of the mediation room, and executing caucuses—significantly contributed to a spike in successful mediations in 2025. Structurally, increasing the number of certified non-judicial mediators is essential to balance the heavy caseload and preserve family institution stability. This research implies that perjudicial mediation requires a psychological approach rather than just administrative fulfillment.